The Glacier Creek Cu-Zn VMS Deposit, Southeast Alaska: An Addition to the Alexander Triassic Metallogenic Belt - Steeves, Nathan J.; Hannington, Mark D.; Gemmell, J. Bruce; Green, Darwin; McVeigh, Garfield (Economic Geology, 2016)
The Glacier Creek volcanogenic massive sulfide (VMS) deposit, Alaska, is hosted within Late Triassic, oceanic back-arc or intraarc, rift-related bimodal volcanic rocks of the allochthonous Alexander terrane, known as the Alexander Triassic metallogenic belt. The Alexander Triassic metallogenic belt is host to the world-class Greens Creek Zn-Pb-Ag VMS deposit near Juneau in the south and the giant Windy Craggy Cu-Co VMS deposit in British Columbia, about 250 km to the north. The Glacier Creek deposit, located ~80 km southeast of Windy Craggy, consists of four tabular massive sulfide lenses within a bimodal mafic volcaniclastic and rhyolitic sequence. The mineralization-hosting stratigraphy is folded by a deposit-scale anticline and offset by a thrust fault near the axial surface of the fold. A resource of 8.13 Mt has been inferred from drilling, with grades of 1.41% Cu, 5.25% Zn, 0.15% Pb, 0.32 g/t Au, and 31.7 g/t Ag. Six main mineralization types are recognized, dominated by massive barite-sphalerite-pyrite, which is replaced at the base and center of the main lenses by massive and semimassive chalcopyrite-pyrite-quartz. The flanks and tops of the lenses are carbonate rich and consist of interbedded calcite-dolomite, barite and sulfide, resedimented massive barite-sulfide, and mineralized massive carbonate rocks. Tuffaceous hydrothermal sediment, with a distinct positive Eu anomaly, overlies the massive sulfide. Pyrrhotite and chalcopyrite in stringers constitute the main “feeder zone.” Stringer-style sphalerite-pyrite mineralization occurs above and below the lenses. Fe-poor sphalerite is dominant throughout the lenses, whereas Fe-rich sphalerite occurs at the stratigraphic top and bottom of the lenses in pyrrhotite-rich zones. Galena, tennantite-tetrahedrite, and arsenopyrite are the most important trace minerals within massive barite-sphalerite-pyrite mineralization, which is generally enriched in Sb, Hg, and Tl. Mineralization-related gangue minerals include barite, quartz, barian muscovite, calcite, ...